1984
DOI: 10.1093/oxfordjournals.eurheartj.a061704
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of aneurysm of the thoracic aorta. Comparison between two non invasive techniques: two-dimensional echocardiography and computed tomography

Abstract: In order to assess the respective values of two-dimensional echocardiography (2D echo) and computed tomography (CT) in the evaluation of aneurysms of the thoracic aorta, 14 patients with angiographically proven aneurysms of the thoracic aorta (three of which were dissecting aneurysms) were studied. The entire thoracic aorta was visualized in 10/14 patients by 2D Echo and in all patients by CT. An intimal flap was recognized by 2D echo in each case with a dissection whereas such a recognition was never possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 0 publications
1
14
0
2
Order By: Relevance
“…As has been described in previous angiographic,42 echocardiographic, [20][21][22] and computed tomographic43,44 studies after surgery or medical therapy, a persistence of the false lumen was found in 78% of the patients in whom the false lumen had not been completely resected during surgery. Furthermore, a persistence of flow within the false lumen was shown in all of these patients.…”
Section: Complicationssupporting
confidence: 61%
“…As has been described in previous angiographic,42 echocardiographic, [20][21][22] and computed tomographic43,44 studies after surgery or medical therapy, a persistence of the false lumen was found in 78% of the patients in whom the false lumen had not been completely resected during surgery. Furthermore, a persistence of flow within the false lumen was shown in all of these patients.…”
Section: Complicationssupporting
confidence: 61%
“…The TEE technique with color Doppler imaging has higher diagnostic reliability than YFE6 9,26,27; TEE avoids inherent limitations of the transthoracic approach such as obesity, narrow intercostal spaces, pulmonary emphysema, and mechanical ventilation by allowing the thoracic aorta to be scanned in multiple sections from close vicinity. '6,28 Moreover, the feasibility of TEE in the setting of aortic dissection and its superiority to conventional radiographic techniques have been demonstrated.…”
Section: Methodsmentioning
confidence: 99%
“…The visualization of an intimal flap that separates the true and false lumens within the aorta is pathognomonic of aortic dissection [66] as shown in Figure 4 and Figure 5. The two-dimensional echocardiography appears to be superior [67] There are 3 types of intimal flap were identified as shown in Table 5.…”
Section: Echocardiographic Featuresmentioning
confidence: 99%